Development of an Online Livestock Showroom to Enhance the Competitiveness of Local Farmers In Blora - Sri Pantja Madyawati; Imam Mustofa; Pudji Srianto; Ali Saifudin (Jurnal Pengabdian Masyarakat Charitas, 2025)
The online livestock showroom development program aims to cut the long livestock distribution chain and create a more objective pricing system, especially for farmers in Blora Regency. The main partners of this activity are local farmers who are members of the Farmer Groups and Blora Livestock Community. The implementation method of the program involves training, mentoring, and collaboration with the government and the farming community. The results show that the showroomternak.id platform successfully improved marketing efficiency, expanded market access, and provided a more transparent pricing system based on morphometric data. As many as 87% of farmers responded positively to this application, and most were satisfied with the ease and fairness in pricing. However, we must still to address challenges like limited internet access and low technological skills. The recommendations from this program are the expansion of training, the improvement of digital infrastructure, and ongoing support for farmers to maximize their use of technology in the long term.